Single-access laparoscopic approach in the surgical treatment of endometrial cancer: A single-institution experience and review of literature - Giacomo Corrado; Giuseppe Cutillo; Giulia Pomati; Emanuela Mancini; Ermelinda Baiocco; Lodovico Patrizi; Maria Saltari; Francesco Barletta; Fabiola Patani; Enrico Vizza (Journal of Minimal Access Surgery, 2016)
Background: The aim of this study was to assess the surgical and oncological outcome for the management of endometrial cancer (EC) by laparoendoscopic single-site surgery (LESS). Patients and Methods: We performed a retrospective chart review of patients who underwent a LESS for EC. All the patients were treated by the same surgical team between July 2009 and June 2013 at the Gynaecologic Oncologic Unit, Regina Elena National Cancer Institute, Rome, Italy. Results: A total of 50 women were included, with a median age of 45 years (range, 39-84 years) and a median body mass index (BMI) of 21.8 kg/m2 (range, 19-48 kg/m2). Median operative time was 100 min (range, 50-240 min), median blood loss was 90 mL (range, 10-300 mL) and median hospital stay was 3 days (range, 2-9 days). The median number of pelvic lymph nodes retrieved was 14 (range, 5-20). No intraoperative complications occurred, but there were 4 postoperative complications. Two patients required a laparoscopic conversion. The median follow-up was 36 months (range, 16-62 months) and no recurrence occurred. Conclusion: Our report showed that the LESS approach in the treatment of early EC can be a safe and reliable technique in terms of surgical and oncological outcomes.